2017
DOI: 10.1093/mnras/stx191
|View full text |Cite
|
Sign up to set email alerts
|

Gas around galaxy haloes - III: hydrogen absorption signatures around galaxies and QSOs in the Sherwood simulation suite

Abstract: Modern theories of galaxy formation predict that galaxies impact on their gaseous surroundings, playing the fundamental role of regulating the amount of gas converted into stars. While star-forming galaxies are believed to provide feedback through galactic winds, Quasi-Stellar Objects (QSOs) are believed instead to provide feedback through the heat generated by accretion onto a central supermassive black hole. A quantitative difference in the impact of feedback on the gaseous environments of starforming galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
5
24
0
Order By: Relevance
“…Directly related to the HI content of CGM and IGM surrounding galaxies, the average Lyα absorption profile is another very well-studied statistic. Large-volume hydrodynamic simulations with various feedback implementations have been employed in several works (Kollmeier et al 2003(Kollmeier et al , 2006Rakic et al 2012Rakic et al , 2013Meiksin et al 2014Meiksin et al , 2015Meiksin et al , 2017Turner et al 2017, see also Chung et al 2019 for a related study with zoom-in simulations) aiming at reproducing measurements of the Lyα flux decrement around LBGs (Adelberger et al 2003(Adelberger et al , 2005Steidel et al 2010;Crighton et al 2011;Rakic et al 2012;Turner et al 2014) and/or QSOs (Prochaska et al 2013b). Except for data points within the virial radius of foreground objects, these observations were generally matched by the simulations.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Directly related to the HI content of CGM and IGM surrounding galaxies, the average Lyα absorption profile is another very well-studied statistic. Large-volume hydrodynamic simulations with various feedback implementations have been employed in several works (Kollmeier et al 2003(Kollmeier et al , 2006Rakic et al 2012Rakic et al , 2013Meiksin et al 2014Meiksin et al , 2015Meiksin et al , 2017Turner et al 2017, see also Chung et al 2019 for a related study with zoom-in simulations) aiming at reproducing measurements of the Lyα flux decrement around LBGs (Adelberger et al 2003(Adelberger et al , 2005Steidel et al 2010;Crighton et al 2011;Rakic et al 2012;Turner et al 2014) and/or QSOs (Prochaska et al 2013b). Except for data points within the virial radius of foreground objects, these observations were generally matched by the simulations.…”
Section: Introductionmentioning
confidence: 83%
“…The majority of past numerical studies of the CGM were mainly concerned with reproducing the covering factor of optically thick absorbers around galaxies and QSOs in the redshift range z ∼ 2 − 3. While recent simulations (Ceverino et al 2012;Dekel et al 2013;Shen et al 2013;Meiksin et al 2015;Suresh et al 2015;Meiksin et al 2017;Suresh et al 2019) were able to broadly reproduce Rudie et al (2012) measurements of this quantity around galaxies, the high covering factor observed around QSOs by Prochaska et al (2013b) proved to be harder to reproduce (Fumagalli et al 2014;Faucher-Giguère et al 2015). Later, Faucher-Giguère et al (2016) was able to recover such measurements with the FIRE zoom-in simulations (Hopkins et al 2014), which included only stellar feedback, arguing that high resolution was a crucial element to obtain this result.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Faucher-Giguère et al (2016) and Meiksin, Bolton & Puchwein (2017) also concluded that simulations employing strong feedback can reproduce the observations. For metal-line absorption, z < 1 O VI observations from Tumlinson et al (2011) and Prochaska et al (2011) have proven challenging for simulations to reproduce (Suresh et al 2017;Oppenheimer et al 2016), though the correspondence is better for low ions, perhaps due to a paucity of hot gas in the models (Hummels et al 2013;Ford et al 2016).…”
mentioning
confidence: 90%